Impact of traffic noise on bird populations in Kinabalu Park, Sabah, Malaysia - Auddrey ambrose (2018)
Kinabalu Park is well-known as one of the best eco-tourist destinations in the world. This park contains a high diversity of flora and fauna, in addition to its outstandingly scenic mountainous landscape with Mount Kinabalu, the highest mountain in the Malay Archipelago, as its backdrop. Many tourism activities related to natural resources can be carried out in this park, such as birdwatching. The bird diversity in Kinabalu Park is exceptionally high, including many species that are endemic to this area. Since its establishment as the first national park in Malaysia in 1964, the number of tourist visiting this park has increased exponentially. Areas inside the park are accessible via an excellent network of paved roads, and over the years this has resulted an increasing level of mechanical disturbance in the form of noise emitted by motorized vehicles (i.e. traffic noise) inside the park area. This study was conducted to investigate the impack of traffic noise on bird’s populations in Kinabalu Park area. The specific objectives were (1) to determine the bird’s species richness and bird’s abundance that present in high traffic noise and low traffic noise; (2) to investigate the impact of traffic noise on bird populations in terms of bird’s species and bird’s abundance. Three levels of traffic noise intensity were used in this study i.e. high traffic noise – defined as noise level ≥60dB, low traffic noise – defined as noise level < 60dB, and areas with no or minimal traffic noise serving as a control treatment. Four sampling sites were selected in this study, all of which were located along man-made trails inside the forests, within the Kinabalu Park area. The high and low traffic noise treatment were represented by three sites, arranged in a pairwise manner; and the control treatment was represented by one site. In order to address the objectives of this study, three different approaches were used i.e. (1) traffic noise mapping by Radioshake Sound Level Meter; (2) bird survey by using point count method; and (3) vegetation survey by enumerating all trees ≥10 cm DBH within the vegetation plots. Data gathered were analyzed using descriptive statistics, diversity index and regression analysis. Overall, a total of 1150 individual of birds were recorded representing 33 species and 20 families. Results of data analysis showed that species richness and diversity of birds in low traffic noise areas were significantly higher than in the high traffic noise areas. Moreover, a significant negative relationship was detected between traffic noise levels and bird’s species richness and abundance. The results of this study generally suggest that traffic noise is an important factor that affects the bird’s population. Therefore, this finding helps the Kinabalu Park Headquarters to better manage the park by taking into account the traffic noise as well as wildlife preservation.